Married Life - Freidrich, Liz (Franklin Watts, 1989)
Advice for teens contemplating marriage on such aspects as reasons for marrying, the wedding, finding a home, budgeting, sex, inlaws, having children, nurturing a relationship, and marital problems.
Keywords: Family; Juvenile Nonfiction; Marriage & Divorce